Frequency of Anterior Knee Pain (AKP) in Different Gender Groups after Total Knee Replacement (TKR) - Sajawal Khan, Muhammad Hanif, Mohammad Ishaq, Usmanullah, Ghareeb Ullah, Jamshed Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Anterior Knee Pain (AKP) is one of the most common causes of persistent problems after knee replacement. Total Knee Arthroplasty (TKA) is a surgical procedure in which artificial joint or prosthesis replace the damage knee. A significant proportion of the patients experience AKP after surgery. Objective: To find out the frequency of Anterior Knee Pain after Total Knee Arthroplasty. Study Setting: Department of Orthopedics, KTH Khyber Teaching Hospital, Peshawar. Study Design: A Cross sectional study. Study Duration: June -2020 to February -2021. Subjects and Methods: After recording complete history, physical examination and routine baseline investigations were done. Patients were put on OT list and surgeries were performed in all patients by expert orthopedic surgeon designated for performing total knee arthroplasty. Post-operatively, patients were kept under observations for 5 days in ward and were discharged if indicated. Patients were followed at regular intervals and finally at the end of 3rd month to measure the intensity of pain on VAS. Results: Out of 205 patients, 69.3% were males and 30.7% were females. Means ± SD calculated for age was 48.62±7.98 years, for BMI was 24.63±3.07 and for Pain on VAS was 1.31±1.39. Most patients (51.7%) were recorded in 51-60 years age group. Rheumatoid Arthritis (RA) in 18% while Osteoarthritis (OA) was found in 82% patients. 21.5% patients were diabetic while 31.7% patients were hypertensive. AKP at 3rd month was found in 8.8% patients. Conclusion: It is evident that anterior knee pain (AKP) after the total knee arthroplasty (TKA), or total knee replacement (TKR) is prevalent and clinically relevant. There is an absolute need for further investigations to find out ways to decrease or eliminate the AKP after TKA in order to improve the quality of life after this surgery. Keywords: Anterior Knee Pain, Total Knee Replacement, Total Knee Arthroplasty.